Pengelolaan Pembelajaran Matematika Di Sekolah Dasar Negeri Gebang Surakarta - Daryanti, Ninik; , Prof. Dr. Budi Murtiyasa; , Dr. Sumardi, M.Si (2017)
Ninik Daryanti. Q100130082. Mathematics Learning Management in Public Elementary School Gebang Surakarta. Thesis. Education administration. Graduate School. Muhammadiyah University of Surakarta. 2016. This study aimed to describe: 1) To describe the planning of mathematics in primary schools Gebang Surakarta. 2) To describe the implementation of mathematics in primary schools Gebang Surakarta. 3) To describe the evaluation of learning mathematics in elementary school Gebang Surakarta. This research use descriptive research, using descriptive qualitative research design. Implementation of this research is in the public elementary school Gebang Surakarta. The research was carried out for six months, since July s / d in December 2016. The data used in this study are primary data and secondary data. Sources of data obtained through interview, observation and documentation. As a guest speaker in this study is the teacher and the Head of State Elementary School Gebang Surakarta. The validity of the data used in this research is triangulation and source triangulation method. Data were analyzed using interactive analysis (model intertwined), which consists of three components: data reduction, data presentation and conclusion. Based on the results of data analysis and discussion we concluded that: 1) Planning learning mathematics in primary schools Gebang Surakarta carried out by preparing the learning device that consists of the annual program, the semester program, the calculation of effective weeks, the development of syllabi and assessment systems, and learning implementation plan ( RPP), while for enrichment and remedial programs some teachers have already made and there is not yet made. The preparation of mathematics learning tool was created by the teacher at the beginning of the semester and supervised by the principal. 2) Implementation of mathematics in primary schools Gebang Surakarta implemented PAIKEM approach, the teacher uses a variety of teaching methods. Learning methods used include learning model with a lab, classroom discussions, demonstrations, delivery of student's work, as well as learning pack in the form of games (game). The role of teachers in mathematics as facilitators, while students play an active role in the learning process. Teachers in implementing the learning in students of inclusion treated the same as other students, both about the evaluation and assessment. 3) Evaluation of learning mathematics in primary schools Gebang Surakarta implemented by using this type of evaluation in written, oral and assignment, this evaluation is done by the teacher conducted at the end of the meeting. Evaluation form assignment given by the teacher conducted individually and in groups.